RADAR SLOPE MANAGEMENT AT NCHANGA OPEN PIT MINE ZAMBIA: FOOTWALL FAILURE OF NOVEMBER 2014 - S Silwamba C,Chileshe P R K (International Journal of Research Science and Management, 2016)
Since 10 fatalities due to one slope failure in April 2001, pit slope management strategy at KCM Nchanga Open Pit [NOP] has been based on slope stability radar for generation of slope performance indicators for management response.The radar for near ‘real time’ data capturing capability wasfirst acquired and implemented at NOP in 2002 and has been successfully used at the mine site to predict slope failures with high potential impact on both economy and safety of life.However,at about 23:15 hours on the 14th November, 2014a major slope failure of about nine hundred thousand tonnes of back fill material occurred from the footwall side resulting in three 240t Komatsu 830E trucks being partially buried. This failure was against the background that the latest recorded radar deformation rates monitored at 09:00hours on the same day of failure indicated that deformation rates were within normally acceptable limits. The main objectives of this paper were to: 1. Understandthe failure mechanism for the 14th November, 2014 footwall slough. 2. Suggest a secondary slope failure prediction philosophy at the mine site using alternative methodologies to the Slope Stability Radar (SSR) ®. 3. Identify options for maximum impact on water management strategies. The pattern of deformation rates showed a lesser degree of deformation in the upper portions of the slope while a larger degree of movement was taking placein the mid-slope and at the toe, which suggested a two phase failure mechanism. The toe of the slope moving first, followed by the mid-slope and upper portions of the slope is the failure mechanism which took place on the November, 2014 slope failure at Nchanga mine.